The Adjustment / Satisfaction Test (A/St) for the subjective evaluation of dialogue enhancement - Torcoli, Matteo; Herre, Jürgen; Paulus, Jouni; Uhle, Christian; Fuchs, Harald; Hellmuth, Oliver (143rd Audio Engineering Society Convention 2017, AES 2017, 2017)
Media consumption is heading towards high degrees of content personalisation. It is thus crucial to assess the perceptual performance of personalised media delivery. This work proposes the Adjustment / Satisfaction Test (A/ST), a perceptual test where subjects interact with a user-adjustable system and their adjustment preferences and the resulting satisfaction levels are studied. We employ the A/ST to evaluate an object-based audio system which enables the personalisation of the level ratio between dialogue and background, i.e., a Dialogue Enhancement system. Both the case in which the original audio objects are readily available and the case in which they are estimated by blind source separation are compared. Personalisation is extensively used, resulting in clearly increased satisfaction, even in the case with blind source separation.
CRIS-Team Scopus Importer:2023-02-20